2017
DOI: 10.1186/s12879-016-2177-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled clinical trial to assess the safety and effectiveness of a novel dual-action oral topical formulation against upper respiratory infections

Abstract: BackgroundCurrent prevention options for upper respiratory infections (URIs) are not optimal. We conducted a randomized, double-blinded, placebo-controlled pilot clinical trial to evaluate the safety and efficacy of ARMS-I™ (currently marketed as Halo™) in the prevention of URIs.MethodsARMS-I is patented novel formulation for the prevention and treatment of influenza, comprising a broad-spectrum antimicrobial agent (cetylpyridinium chloride, CPC) and components (glycerin and xanthan gum) that form a barrier on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 44 publications
2
50
0
13
Order By: Relevance
“…Preservatives like cetylpyridinium chloride are used in lignocaine preparations, which have antimicrobial properties [12]. These facts prompted us towards a theoretical concern of tampered sample quality with lignocaine usage.…”
Section: Discussionmentioning
confidence: 99%
“…Preservatives like cetylpyridinium chloride are used in lignocaine preparations, which have antimicrobial properties [12]. These facts prompted us towards a theoretical concern of tampered sample quality with lignocaine usage.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, in a pilot double-blinded, placebo-controlled, randomized clinical trial, assessing a CPC-based formulation for inhalation, in the prevention of upper respiratory tract infections (usually associated with influenza virus, RSV, human metapneumovirus (hMPV), rhinovirus, and adenovirus), it was observed that patients in the test group suffered viral infections with less severity and duration, when compared with those included in the placebo group [39].…”
Section: Povidone-iodinementioning
confidence: 99%
“…33 The antiviral effect of CPC has been demonstrated in influenza patients, significantly reducing the duration and severity of cough and sore throat. 31,34 Hypotheses about a possible action over SARS-CoV-2 are based on its lysosomotropic mechanism of action and its ability to destroy viral capsids. 35 These findings indicate that CPC could be effective against other enveloped viruses such as coronaviruses.…”
Section: Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%